Parenting Styles and Self-Help Skills of Kindergarten Learners - Sobrebiga, Pamela Joie T.; Medez, Sharon Rose G. (Philippine Social Science Journal, 2020)
Parenting style has influenced children’s development, particularly on behavior development and school readiness among kindergarten learners. It is a strong predictor not only of the cognitive but also of the social-emotional developmental success in children. Quality care for children during the early years of development has been emphasized. To achieve developmental outcomes, children should develop independence by acquiring self-help skills or self-care skills, which enable them to look after themselves and socialize daily. Studies have associated parenting styles with the academic performance and social-emotional behavior of children; however, the literature on parents’ role, particularly on children’s self-help skills, is very limited. This study assessed the dominant parenting styles of a district in Negros Occidental during the school year 2018-2019 and the learners’ level of self-help skill. It determined the differences in the learners’ self-help skills regarding the parents’ sex, family monthly income, employment status, marital status, and the relationship between parenting styles and self-help skills.